2014
DOI: 10.1007/s13205-014-0255-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Klebsiella granulomatis pathogenic to silkworm, Bombyx mori L.

Abstract: Bacterial disease of silkworm causes significant reduction of silk production leading to huge economic loss. This study aims to isolate bacteria from diseased silkworm and to determine its pathogenicity and antibiotic resistance. A strain of Klebsiella granulomatis has been isolated from silkworm haemolymph which was later identified on the basis of biochemical tests and 16S rRNA gene sequencing. The optimum culture condition of K. granulomatis was determined at pH 7.0 and 37 °C temperature. The strain was res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…This result was in agreement with the earlier reports as demonstrated in bacterial infections in other silkworms (Choudhury et al, 2004;Mohanta et al, 2014;Jurat-Fuentes and Jackson, 2012). It was further found that pathogens could kill 50 to 90% of silkworms within four days either by injection or oral administration of the inoculums.…”
Section: Discussionsupporting
confidence: 93%
“…This result was in agreement with the earlier reports as demonstrated in bacterial infections in other silkworms (Choudhury et al, 2004;Mohanta et al, 2014;Jurat-Fuentes and Jackson, 2012). It was further found that pathogens could kill 50 to 90% of silkworms within four days either by injection or oral administration of the inoculums.…”
Section: Discussionsupporting
confidence: 93%
“…Then, the top phase was transferred to a fresh tube, and the DNA was precipitated with isopropanol and later re-suspended in TE buffer (pH 7.4). Next, 16S rDNA was amplified by polymerase chain reaction (PCR) using universal forward 16SF (5′-GAGTTTGATCCTGGCTCAG-3′) and reverse 16SR (5′-GAAAGGAGGTGATCCAGCC-3′) primers (Mohanta et al, 2015 ). The PCR reactions were 25 μl and contained 5 μl of 5 × buffer (TaKaRa Bio Inc.), 0.5 μl of dNTP mixture (10 mM of each dNTP, TaKaRa Bio Inc.), 1 μl of 2% BSA (Promega), 0.5 μl of forward primer (10 μM), 0.5 μl of reverse primer (10 μM), 0.125 μl of One Taq DNA Polymerase (New England Biolabs), 15.375 MQ and 2 μl of template DNA.…”
Section: Methodsmentioning
confidence: 99%
“…The symptoms of the silkworms were observed and the mortality of the silkworms was recorded. Data were analyzed using SPSS 20, and the median lethal concentration (LC 50 ) was obtained ( Mohanta et al. 2014 ).…”
Section: Methodsmentioning
confidence: 99%